Long-Term Anatomic and Functional Outcomes after Macular Hole Surgery - Karolina Kaźmierczak; Joanna Stafiej; Joanna Stachura; Paweł Żuchowski; Grażyna Malukiewicz (Journal of Ophthalmology)
Aim. To evaluate the structural and functional outcomes in patients who underwent macular hole (MH) surgery in the long-term follow-up. Materials and Methods. Forty-four eyes of 40 patients (28 females and 12 males) were examined. The examination included visual acuity, optical coherence tomography, and colour vision testing. The same evaluation was performed in 30 fellow eyes. Results. MH closure was obtained in 42 eyes (95.45%). There was no reopening of the initially closed MHs. In long-term postoperative examination, we observed IS/OS junction defects in 28 (63.6%) eyes and ELM defects in 19 (43.2%) eyes. We found that the IS/OS junction defects correlated with the diameter of the MH (p=0.016), whereas ELM defects correlated with both the diameter of the MH (p=0.001) and duration time of the MH (p=0.008). The presence of ELM defects in OCT was the cause of inferior BCVA in long-term observation time (p=0.004). The mean BCVA before the MH surgery was 0.15. It improved significantly both in early (p<0.001) and long-term postoperative observation (p<0.005). Generally, the functional outcomes were better in eyes with short-time duration of the MH, when a smaller diameter (<400 μm) of the hole was measured and a V-shaped closure of the MH and the restoration of the ELM line on OCT were present. Pseudoprotanomaly was noted in 13 (35.1%) eyes. In the fellow eye group, mean BCVA was 0.95 (range, 0.6–1.0). In 3 eyes, we detected vitreomacular traction, and in 4 eyes, initial cataract. These conditions, as well as probably early stage of diabetes mellitus, influenced functional outcomes of studied eyes. Conclusions. The anatomic and functional outcomes after macular surgery are satisfactory and improve with time. After a successful closing of the MH, the restoration of the retina progresses at a slower pace than improvement in visual acuity.